2020
DOI: 10.3389/fpsyt.2020.00151
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Deleterious Single-Nucleotide Polymorphisms Associated With Antidepressant Efficacy in Major Depressive Disorder

Abstract: Major depressive disorder (MDD) is a serious mental disease with negative effects on both mental and physical health of the patient. Currently, antidepressants are among the major ways to ease or treat MDD. However, the existing antidepressants have limited efficacy in treating MDD, with a large fraction of patients either responding inadequately or differently to antidepressants during the treatment. Pharmacogenetics studies have found that the genetic features of some genes are associated with the antidepres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…This is supported by the fact that rs1065852 is located in a conserved region of CYP2D6 and therefore, possibly important for protein function [32]. Modeling studies showed that the flexibility in the F-G loop, which may affect the entrance of a substrate into the protein, is lower in the mutant than the wild type, which may account for lower enzyme activity [32]. Consistent with this observation, in a previous genome-wide association study, rs1065852 was found to be associated with the metabolism of escitalopram [33].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This is supported by the fact that rs1065852 is located in a conserved region of CYP2D6 and therefore, possibly important for protein function [32]. Modeling studies showed that the flexibility in the F-G loop, which may affect the entrance of a substrate into the protein, is lower in the mutant than the wild type, which may account for lower enzyme activity [32]. Consistent with this observation, in a previous genome-wide association study, rs1065852 was found to be associated with the metabolism of escitalopram [33].…”
Section: Discussionmentioning
confidence: 93%
“…Carriers of the A-allele showed higher serum concentrations of amitriptyline then the wild type (G). This is supported by the fact that rs1065852 is located in a conserved region of CYP2D6 and therefore, possibly important for protein function [32]. Modeling studies showed that the flexibility in the F-G loop, which may affect the entrance of a substrate into the protein, is lower in the mutant than the wild type, which may account for lower enzyme activity [32].…”
Section: Discussionmentioning
confidence: 99%
“…Age of onset of MDD Saus et al, 2010 Interaction of rs6782799, rs6265 (BDNF), and negative life events MDD Yang et al, 2010BDNF rs6265 MDD Tsai et al, 2003Schroter et al, 2020 Interaction of rs6265 and stressful life events MDD Hosang et al, 2014 rs6265 Recurrent MDD Xiao et al, 2011;Lee Y. et al, 2013 rs6265 Severity of depression Losenkov et al, 2020 rs6265 Response to antidepressant therapy and remission in MDD Choi et al, 2006;Alexopoulos et al, 2010;Chi et al, 2010;Zou et al, 2010;Taylor et al, 2011;Murphy et al, 2013;Wang et al, 2014;Colle et al, 2015;Xin et al, He et al, 2007 Various intronic deletions and insertions 29 bp from the exon 9-intron 9 junction BD Stopkova et al, 2003 FIGURE 1 | Shown are molecular interactions involving protein products of PIP4K2A and NRG1 associated with time to recurrence of an episode in bipolar disorder and antidepressant treatment response. Phospholipids phosphatidylinositol-5-phosphate (PI5P) and phosphatidylinositol-5,4-bisphosphate (PIP2) are located on the intracellular leaflet of the plasma membrane, while the channel KCNQ and the receptor ERBB4 are transmembrane.…”
Section: Gsk3b Rs6438552mentioning
confidence: 99%
“…In addition to various environmental, physiological, and psychological factors, these individual differences might be largely due to genetic factors [3,4]. Therefore, various pharmacogenetic studies have been conducted to identify genetic variants that can predict patients who may optimally benefit from specific, individually tailored treatments [5][6][7][8][9] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%